Effect of Folded Structures on Interfacial Solar-Driven Seawater Desalination - Shufang Zhu; Yuke Niu; Xu Yan (Membranes)
Currently, solar-driven interface evaporation for seawater desalination is believed to be an effective way to overcome freshwater shortage. To improve the efficiency of solar-driven interfacial evaporators, designing the evaporator’s structure is essential. In this study, we proposed a folded structure solar-driven interfacial evaporator with electrospun recycled PET/carbon nanotube fibrous membranes. The as-spun membranes were folded into 4, 8, and 16 petals. The results suggested that F@8 (fold with eight petals) had the best solar-driven evaporation performance, with a photothermal conversion efficiency of 90.59% and an evaporation rate of 1.31 kg·m−2·h−1, due to its lower light projection area and greater light absorption. The evaporation performance remained stable after 10 cycles. In addition, the concentration of ions in the freshwater collected after desalination was 2~3 orders of magnitude lower than that before desalination. These results indicate that a properly designed folded structure can effectively enhance evaporators through changing the light projection area and absorption. This approach might provide an effective way to optimize the structure of interfacial solar-driven evaporators.